PET Imaging of Astrogliosis and Tau Facilitates Diagnosis of Parkinsonian Syndromes - Schönecker, Sonja; Brendel, Matthias; Palleis, Carla; Beyer, Leonie; Höglinger, Günter U.; Schuh, Elisabeth; Rauchmann, Boris-Stephan; Sauerbeck, Julia; Rohrer, Guido; Sonnenfeld, Stefan; Furukawa, Katsutoshi; Ishiki, Aiko; et al. (Frontiers in Aging Neuroscience, 2019)
Neurodegenerative parkinsonian syndromes comprise a number of disorders that are characterized by similar clinical features but are separated on the basis of different pathologies, i.e. aggregates of α-synuclein or tau protein. Due to the overlap of signs and symptoms a precise differentiation is often difficult, especially early in the disease course. Enormous efforts have been taken to develop tau-selective PET imaging agents, but strong off-target binding to MAO-B has been observed across first generation ligands. Nonetheless, astrogliosis related MAO-B elevation is a common histopathological known feature of all parkinsonian syndromes and might be itself an interesting imaging target. Therefore, this study aimed to investigate the performance of [18F]-THK5351, a combined MAO-B and tau tracer for differential diagnosis of parkinsonian syndromes. [18F]-THK5351 PET was performed in 34 patients: six with Parkinson’s disease (PD), nine with multiple system atrophy with predominant parkinsonism (MSA-P), six with MSA with predominant cerebellar ataxia (MSA-C) and 13 with progressive supranuclear palsy (PSP) Richardson’s syndrome. Volume-of-interest based quantification of standardized-uptake-values was conducted in different parkinsonian syndrome related target regions. PET results were subjected to multinomial logistic regression to create a prediction model discriminating among groups. Furthermore, we correlated tracer uptake with clinical findings. Elevated [18F]-THK5351 uptake in midbrain and diencephalon differentiated PSP patients from PD and MSA-C. MSA-C patients were distinguishable by high tracer uptake in the pons and cerebellar deep white matter when compared to PSP and PD patients, whereas MSA-P patients tended to show higher tracer uptake in the lentiform nucleus. A multinomial logistic regression classified 33/34 patients into the correct clinical diagnosis group. Tracer uptake in the pons, cerebellar deep white matter and striatum was closely associated with the presence of cerebellar and parkinsonian symptoms of MSA patients. The current study demonstrates that combined MAO-B and tau binding of THK5351 facilitates differential diagnosis of parkinsonian syndromes. Furthermore, our data indicate a correlation of MSA phenotype with [18F]-THK5351 uptake in certain brain regions, illustrating their relevance for the emergence of clinical symptoms and underlining the potential of THK5351 PET as a biomarker that correlates with pathological changes as well as with disease stage.